Omni-joint; proof of concept & comparative Study - AboZaied, AbdAllah Ezzat (AUC Knowledge Fountain, 2019)
Robots mainly consist of links and joints, hence studying different joints and coming up with new joints will contribute in advancing robots. The methodology used in this thesis is; Proofing the concept of the Omni-Joint by theoretical analysis and manufacturing a prototype, comparing the following revolute joints; Omni-Joints, Hooke's joint, and Ordinary joint. The comparison is regarding; points of singularity, range of field of motion, inverse kinematics and applying it on different paths using MATLAB, and finally studying the stresses on the Omni-Joint using FEM with CAD software AutoDesk-Inventor in different postures. The results are that unlike the Ordinary-joint and the Hooke-joint the Omni-Joint has; no singularities, continues range of field of motion, simple one to one kinematics.